Status Of Haemorrhagic Septicemia In Cattle And Buffalo In Uttar Pradesh, India (Applied Biological Research, 2011)
The investigation was undertaken to assess the status of haemorrhagic  septicaemia (HS) in cattle and buffalo in Uttar Pradesh (India).  Conventional methods were used for the diagnosis of HS and counter  immunoelectrophoresis (CIE) method for epidemiological and capsular  typing of Pasteurella multocida, the organism involved in HS. A total of 25  isolates were obtained and identified as P. multocida serotype B. The  isolates were recognized into 12 biotypes on the basis of sugar  fermentation tests thus indicating the involvement of multiple strains of P. multocida serotype B in the study area. Bipolar characteristic was exhibited in 25 samples (blood and impression smears of vital organs).  The presence of antibodies against P. multocida B:2 in 10 (22.2%) serum samples by CIE showed the prevalence of P. multocida B:2 infection in  the area. The results indicated that conventional methods (bipolar  staining and CIE) are useful for rapid epidemiological investigations of  HS.
Keywords: Biotypes; bipolar staining; Counter immuno electrophoresis; haemorrhagic septicaemia; Pasteurella multocida